On the Failure of the Linkage Principle in Multi-unit Auctions - Perry, Motty; Reny, Philip J. (Econometrica, 1999)
It is shown that the linkage principle (Milgrom and Weber (1982)) does not extend to the multi-unit auction setting. An analysis of the equilibium bidding strategies is carried out for the general two-agent/two-unit Vickrey auction in order to provide economic insight into the nature of the failure.